Hubungan Antara Pola Asuh Demokratis dengan Kecerdasan Emosional Pada Remaja di SMA Swasta Al Hikmah - Halfa Rizky; Hairul Anwar Dalimunthe (Universitas Medan Area, 2023)
This study aims to determine the relationship between democratic parenting and emotional intelligence in adolescents at Al Hikmah private high school. The type of research is quantitative research. The population is 80 teenagers. The sample in this study amounted to 49 people with democratic parenting. The measuring instrument used to measure the democratic parenting of adolescents using the scale of democratic parenting from Munandar (in Shochib 2010) is deliberation in the family, controlled freedom, parental direction, guidance and attention, mutual respect between family members, two-way communication. Measuring adolescent emotional intelligence using the emotional intelligence scale from Goleman (2014), namely, self-awareness, self-knowledge, self-motivation, four, social skills. It is known that there is a significant positive relationship between democratic parenting and emotional intelligence with a correlation coefficient of r_xy 0.609 with P = 0.000 0.050. This means that the higher the democratic parenting pattern, the higher the emotional intelligence, or vice versa. The hypothesis is accepted. The effective contribution of democratic parenting variables to students' emotional intelligence is 37.1%. Based on this research, it can be seen that there are still 62.9% influence of other factors on emotional intelligence that are not revealed in this study. The results of the research on students have moderate emotional intelligence and moderate democratic parenting. This can be seen from the SD results of 15.356, the empirical mean value of emotional intelligence of 79.00, and the hypothetical mean of 75. Furthermore, the results of the elementary school of democratic parenting were 13,889, the empirical mean was 75.04 and the hypothetical mean was 85.